Analisis Pengaruh Perspektif Brand Ambassador, Electronic Word Of Mouth (e-WOM) Dan Citra Merek Terhadap Minat Beli Konsumen Pada Sunscreen Azarine (Studi pada Mahasiswa Universitas Islam Malang 2021) - Oktaviani, Alycia Rahma; Salim, Muhammad Agus; Millaningtyas, Restu (UNIVERSITAS ISLAM MALANG, 2025)
Abstract The purpose of this study is to examine how consumer purchase intentions for Azarine sunscreen products are influenced by brand ambassadors, electronic word-of-mouth (e-WOM), and brand image. Azarine sunscreen has been a popular option in Indonesia due to the emergence of several new marketing methods brought about by the growing usage of social media, especially among younger consumers. The methodology employed is quantitative research involving 97 respondents from the 2021 cohort of Universitas Islam Malang, determined using the Slovin formula. Using SPSS 26 and multiple linear regression analysis, it was discovered that brand ambassadors, e-WOM, and brand image all significantly and simultaneously influence consumers' intentions to make purchases.. With a β coefficient of 0.404, the e-WOM variable produced the most significant results, suggesting that e-WOM has a stronger effect on purchase intention than other components. Keywords: Brand Ambassador, Electronic Word of Mouth (e-WOM), Brand Image, Buying Interest, Azarine Sunscreen